(untitled) (Medico Legal Update, 2021)
Objectives: The study aims to assess the level of emotional intelligence among undergraduate medical students and to identify the relationship between the level of emotional intelligence and some demographic variables of the students such as: academic year, gender, residency, and monthly income. Methodology: A descriptive, cross-sectional design that is initiated for the period of January 1st to May 1st, 2018 on a sample consisted of (200) students which was selected by convenient sampling method from four medical colleges at University of Baghdad that are: College of medicine, college of dental medicine, college of pharmacy, and college of nursing. The used questionnaire is divided into two parts; one of them contains the demographic variable of the students and the other one deals with the Scale of Emotional Intelligence (EIS). The data have been collected through the utilization of the self-administrative report as a mean of data collection and analyzed by application of statistical package for social science IBM SPSS (v. 24). Results: The result revealed that student are showing moderate level of emotional intelligence (63.5%). A relationship was detected between students’ gender and his emotional intelligence, while there are no significant relationships between emotional intelligence and academic year, residency, and monthly income. Conclusions: The study concluded that students at medical colleges group are emotionally stable and emotionally intelligent. There is difference in gender of students with regard to emotional intelligence. Recommendations: The study recommended for conducting future related studies with various variables and re-conducting the study on a large sample and different specialties is necessary